A new yellow-flowered ornithophilous Vriesea and an illustrated collection of the bromeliads from Pico Alto, Serra do Baturité, Ceará State, Northeastern Brazil - Versieux, Leonardo M.; Tomaz, Eduardo C.; Fortunato, Márcia; Verola, Christiano (Phytotaxa, 2013)
Vriesea baturitensis is described and illustrated as a new species. It is compared with V. friburgensis and V. rodigasiana, which we consider to be morphologically the most related species. The new taxon occurs in isolated Atlantic forest patches along the Baturité mountain range, in central-north Ceará state, Northeastern Brazil. It is characterized by the compact and regular rosette, a rounded leaf apex, stiff and erect peduncle, peduncle and primary bracts bright yellow, and the particular colors and sizes of the floral bracts and sepals. The humid habitat where the new species was found, known in Brazil as brejo de altitude, is surrounded by the Caatinga (Brazilian dry woodland) and due to its climatic conditions supports a rich flora of epiphytes. In Pico Alto we collected and photographed six different species of bromeliads, two of each being Guzmania and Vriesea, one of each being Aechmea and Racinaea. We conclude that the area of Pico Alto is an important remnant of humid forest and conservation measures to protect its epiphytes are urgently needed.